Corruption as a Contributing Factor to Unemployment and Environmental Pollution in Nigeria: The Niger Delta Perspective - Nzenari, Ugonna Paschal (Journal of Government and Political Issues, 2023)
The need to root out corruption from the system of nations for all round national peace, growth and development cannot be over emphasized. This study has been undertaken to examine corruption as a contributing factor to unemployment and environmental pollution in the Niger Delta Region of Nigeria. Descriptive survey was adopted for the study and multistage sampling techniques was used in the process. The study was narrowed down to two states within the Niger Delta. The population of the study comprised former and present employees of all illegal oil refineries (dumps) within the region. However, the total respondents sampled were two hundred, questionnaire was the instrument used to collect data for the study. The findings of the study include high level of corruption among politica l leaders and public office holders, illegal oil activities as a result of unemployment, crude oil theft and its local distillation process as a major cause of environmental pollution. The study recommended among other things that government should rehabilitate the youths who engage in these activities, recognize their skills and potentials, legalize their activities with strict supervision, and support them with modular refineries to reduce unemployment and dependency on oil importation.